Can Systematic Reviews Inform GMO Risk Assessment and Risk Management? - Kohl, Christian; Frampton, Geoff; Sweet, Jeremy; Spök, Armin; Haddaway, Neal Robert; Wilhelm, Ralf; Unger, Stefan; Schiemann, Joachim (Frontiers in Bioengineering and Biotechnology, 2015)
Systematic reviews represent powerful tools to identify, collect, synthesize and evaluate primary research data on specific research questions in a highly standardized and reproducible manner. They enable the defensible synthesis of outcomes by increasing precision and minimizing bias whilst ensuring transparency of the methods used. This makes them especially valuable to inform evidence-based risk analysis and decision making in various topics and research disciplines. Although seen as a “gold standard” for synthesizing primary research data, systematic reviews are not without limitations as they are often cost, labor and time intensive and the utility of synthesis outcomes depends upon the availability of sufficient and robust primary research data. In this paper we 1) consider the added value systematic reviews could provide when synthesizing primary research data on genetically modified organisms (GMO) and 2) critically assess the adequacy and feasibility of systematic review for collating and analyzing data on potential impacts of GMOs in order to better inform specific steps within GMO risk assessment and risk management. The regulatory framework of the EU is used as an example, although the issues we discuss are likely to be more widely applicable.